Partnering Project Success Criteria in Malaysia - Jusoff, Kamaruzaman; Adnan, Hamimah (2008)
Partnering is used as an approach in the procurement system as it could lead towards improving the performance of the construction industry. Organizations which used the partnering approach in their past construction projects are now reporting favorable results, which include decrease in project costs, delivery of project to program, time quality and buildability. Despite these benefits, there remain are still risks associated with this mode of procurement. Risk management process and partnering are critical to the succession of the construction project. Three (3) case studies were looked into to support this study. The opinions and techniques of risk mitigation were gathered. It was found that the most critical construction partnering risk is the partner’s financial resources, the clients’ problems and economic conditions and financial problems with one of the partner. It is hoped that the risk management programme will help to reduce such risks.